Cloud computing security: A survey of service-based models. Issue 114 (March 2022) - Khoda Parast, Fatemeh; Sindhav, Chandni; Nikam, Seema; Izadi Yekta, Hadiseh; Kent, Kenneth B.; Hakak, Saqib
Abstract: Cloud computing has recently attracted significant attention due to its economical and high-quality services. In the last decade, cloud services have inevitably entangled with businesses' and individuals' daily lives through products and services. On-demand, pay-per-use characteristics encourage corporations to outsource part of their businesses to accelerate their services and multiply value. The latest market tendency toward migration to cloud environments, started in 2019, indicates a flourishing trend in the next few years. Despite the numerous benefits of the cloud computing model for businesses or individuals, security issues still have been stated as the top cloud challenge in 2020. Although various factors affect security, technologies enabling cloud computing such as virtualization and multitenancy, in addition to on-demand characteristics, initiate new security entrances for malevolent activities. In this study, we surveyed service-based cloud computing security issues to establish the current state of the field. The main contribution of this paper is to analyze the state of cloud security in the last decade and provide a unified taxonomy of security issues over the three-layer model, i.e., IaaS, PaaS, and SaaS.